Theoretical mediations for the analysis of the financialization of space production in Latin America (2019)
The article aims to establish dialogical connections between the abstract-theoretical and the concrete-historical planes of the regional and urban manifestations of the financialization process in the capitalist periphery. Referring to the existing literature, it rescues exogenous and endogenous interdependencies that define the specificity of underdevelopment and argues for the need of this analytical interface for an adequate interpretation of space production in Latin American reality. It proposes to qualify the political, economic, social and geographic reach of the contemporary hegemony of interest-bearing capital and highlights the relational, procedural and mediators aspects that imbricate such dimensions in a transscalar approach, based on Brazilian case. It argues that the subsumption of the environment built by the process of financialization deepens the selectivity, the fragmentation, and the exclusion typical of peripheral spatiality.